Deep Water Wind: The Legal Challenges with Harnessing Ocean Wind Potential Through Floating Wind Turbines - Natalie Clarke (Washington University Global Studies Law Review, 2025)
Wind energy technology has undergone continuous advancement, most recently with its expansion into ocean wind harvesting through offshore floating wind technology. As this industry expands, the international legal community has the unique opportunity to proactively establish a comprehensive legal framework for its sustainable and equitable development. Therefore, this note urges the international community to address the foreseeable environmental, political, administrative, and national security issues related to offshore floating wind technology. Offshore floating wind technology should be encouraged as an exciting new renewable energy development. However, it presents legal issues that demand attention. For example, various issues, such as environmental concerns about the potential impacts on marine ecosystems and safety concerns due to conflicts with other high seas uses, highlight the need for a comprehensive and tailored legal framework for offshore floating wind technology. Moreover, the possibility of multi-state energy projects and jurisdictional disputes over wind farm placement underscore the critical need for a legal framework that effectively addresses these political considerations and fosters international cooperation. Lastly, while advancing renewable energy initiatives is commendable, one must prioritize safeguarding critical infrastructure, as energy security and national security are connected. Existing legal frameworks, such as the United Nations Convention on the Law of the Sea (UNCLOS), are insufficient in addressing these challenges and are unlikely to be adequately revised. As such, the international community should explore soft law mechanisms and prioritize the establishment of separate agreements as viable solutions. Additionally, the innovative concept of “friendshoring” should be implemented to enhance international collaboration while simultaneously addressing energy security concerns.
Keywords: wind energy technology; ocean wind harvesting; offshore floating wind technology; sustainable; enviornmental; UNCLOS; friendshoring